2017
DOI: 10.1103/physrevb.95.085118
|View full text |Cite
|
Sign up to set email alerts
|

Electronic band structure for occupied and unoccupied states of the natural topological superlattice phase Sb2Te

Abstract: We present an experimental study describing the effects of surface termination on the electronic structure of the natural topological superlattice phase Sb2Te. Using scanning angle-resolved photoemission microscopy, we consistently find various non-equivalent regions on the same surface after cleaving various Sb2Te single crystals. We were able to identify three distinct terminations characterized by different Sb/Te surface stoichiometric ratios and with clear differences in their band structure. For the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These results were immediately confirmed and further investigated in other studies on Bi 2 Se 3 ; other compounds of the same family were later studied with the same approach, like for instance Sb 2 Te 3 , SnSb 2 Te 4 , where a much faster (sub‐ps) dynamics was instead observed. The continuous discovery of surface topological properties in new classes of materials will contribute to providing a more extensive data set for their ultrafast dynamics properties, as recently demonstrated for novel materials like Zr 2 Te 5 , the superlattice series (Sb 2 ) m ‐Sb 2 Te 3 or Kondo topological insulators like SmB 6 …”
Section: Topological Insulatorsmentioning
confidence: 98%
“…These results were immediately confirmed and further investigated in other studies on Bi 2 Se 3 ; other compounds of the same family were later studied with the same approach, like for instance Sb 2 Te 3 , SnSb 2 Te 4 , where a much faster (sub‐ps) dynamics was instead observed. The continuous discovery of surface topological properties in new classes of materials will contribute to providing a more extensive data set for their ultrafast dynamics properties, as recently demonstrated for novel materials like Zr 2 Te 5 , the superlattice series (Sb 2 ) m ‐Sb 2 Te 3 or Kondo topological insulators like SmB 6 …”
Section: Topological Insulatorsmentioning
confidence: 98%
“…The nature of the interlayer bonding between the blocks differs for Sb and Bi compounds. In the case of antimony tellurides, all three gaps are vdW in nature, ,, and the Sb 2 Te 3 –Sb 2 Te 3 , Sb 2 –Sb 2 , and Sb 2 Te 3 –Sb 2 interlayer distances are 2.7 Å, 2.2–2.3 Å, and 2.4–2.5 Å, respectively. For comparison, the Sb 2 Te 3 –Sb 2 Te 3 interlayer distance is 2.8 Å in the α-Sb 2 Te 3 structure .…”
Section: Post-transition Metal Chalcogenidesmentioning
confidence: 99%
“…Similar to the M V 2 X 3 compounds, members of the (M V 2 ) m (M V 2 X 3 ) n series show topologically nontrivial properties and are thermoelectrics. ,, Different surface terminations and termination-dependent electronic properties have been identified for cleaved Sb 2 Te and Bi 4 Se 3 crystals by ARPES studies where a complex interplay between structure and surface electronic properties was discovered. BiTe was recently discovered to be a dual 3D topological insulator (weak topological insulator and topological crystalline insulator phases simultaneously) and also showed termination-dependent surface states. , These findings suggest ample opportunity for further study of the members of (M V 2 ) m (M V 2 X 3 ) n series in the 2D limit.…”
Section: Post-transition Metal Chalcogenidesmentioning
confidence: 99%
“…Several attempts to decrease the significant bulk carrier contribution were based on chemical doping [15,16], increasing the surface-to-bulk ratio using nanostructur-ing which can be performed through mechanical exfoliation or growth of TI nanowires and nanoribbons [17,18], epitaxial growth of TI/II-VI semiconductor superlattices [19,20], and irradiation by high-energy electron beams: in particular, intrinsic quantum transport measurements and angle-resolved photoemission spectroscopy (ARPES) revealed that a technique based on irradiation with swift (∼ 2.5 MeV energy) electron beams at specific electron doses [21] doesn't affect the Dirac energy dispersionimmmune to disorder-and offers a path to large scale transport in topological SSs. Furthermore, this experimental study has indicated that it is possible, by following a thermal protocol, to tune the band position from the irradiation-induced n-type back towards the charge neutrality point where the system remains for months.…”
Section: Introductionmentioning
confidence: 99%